2004
DOI: 10.1038/labinvest.3700039
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of CD8+ T cells containing RANTES/CCL5+ cytoplasmic granules in actively inflammatory lesions of human chronic gastritis

Abstract: Chronic gastritis is frequently associated with infection of Helicobacter pylori and characterized by tissue infiltration of neutrophils, lymphocytes, and plasma cells. To address the mechanism of lymphocyte infiltration in chronic gastritis, we examined the expression of chemokines and their receptors using frozen sections of chronic gastritis, obtained from 23 patients who underwent gastrectomy for gastric cancer. By immuno histochemistry, lymphocytes in inflamed gastric mucosa expressed CCR5 abundantly, CXC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 32 publications
4
25
0
Order By: Relevance
“…In situ hybridization performed in two cases revealed that some granuloma cells clearly expressed RANTES mRNA (Figure 6c [signals] and d [negative control]). In all eight cases, a part of lymphocytes surrounding granulomas were also positive for the RANTES protein in the cytoplasm with a characteristic dotted pattern 17,19 (Figure 6b, arrows), and also positive for RANTES mRNA in the cytoplasm (Figure 6c, arrowheads). By contrast, lymphocytes in lymphoid aggregates did not stain for RANTES (data not shown).…”
Section: Immunohistochemical Analysis Of Chemokines In Crohn's Diseasementioning
confidence: 91%
See 4 more Smart Citations
“…In situ hybridization performed in two cases revealed that some granuloma cells clearly expressed RANTES mRNA (Figure 6c [signals] and d [negative control]). In all eight cases, a part of lymphocytes surrounding granulomas were also positive for the RANTES protein in the cytoplasm with a characteristic dotted pattern 17,19 (Figure 6b, arrows), and also positive for RANTES mRNA in the cytoplasm (Figure 6c, arrowheads). By contrast, lymphocytes in lymphoid aggregates did not stain for RANTES (data not shown).…”
Section: Immunohistochemical Analysis Of Chemokines In Crohn's Diseasementioning
confidence: 91%
“…15,16 All the immunohistochemical procedures were performed using frozen sections prefixed in PLP. [15][16][17] The primary antibodies used are listed in Table 2. For the secondary antibody, Envision plus kit (DakoCytomation) was used with 3-3 0 diaminobenzidine tetrahydrochloride (DAB; Dojin, Kumamoto, Japan) as a chromogen.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 3 more Smart Citations